Fiqh of Disaster: A Development of Landslide Mitigation-Preparedness Module Based on the Transdisciplinary Islamic Approach - Rahmat Ryadhush Shalihin; Betty Mauli Rosa Bustam; Yudhiakto Pramudya; Suyadi Suyadi (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2022)
AbstractThe purpose of this research is to create a non-formal module on the fiqh of disaster as part of an effort in landslide mitigation-preparedness using a community-oriented in Indonesian society. Indonesia is strategically placed in the ring of fire, making the main areas vulnerable to natural disasters. As one of the most prominent Muslim organizations in Indonesia, Muhammadiyah, with fiqh of disaster attempts to provide direction for society on disaster management based on Islamic norms and regulations. In this study, we use a transdisciplinary Islamic approach within the key fields of Islamic education, Islamic jurisprudence, and disaster jurisprudence, and physics (inclined plane). The research method used in this study is R&D under the ADDIE model, with five steps: analysis, design, development, evaluation, and analysis. This study included data document evaluation and questionnaires as data collection, whereby content analysis, product development, and product feasibility are all data analysis methodologies. The results showed that the module on landslide mitigation for society is well executed. The material examiner obtained a total score of 22 with a percentage of 91% and rated it